Stress-dependent electromechanical properties of doped (Ba1-xCax)(ZryTi1-y)O-3 - Humburg, Heide I.; Acosta, Matias; Jo, Wook; Webber, Kyle Grant; Roedel, Juergen (Journal of the European Ceramic Society, 2015)
The effect of 1 at% Fe- and FeNb-doping on the temperature and stress stability of the electromechanical properties of (Ba1-xCax)(ZryTi1-y)O-3 (BCZT) was investigated. For the composition (Ba0.89Ca0.11)(Zr0.135Ti0.865)O-3 with rhombohedral symmetry, doping reduces the Curie point and the temperature stability of the large-signal electromechanical properties significantly. The large-signal piezoelectric coefficient d(33)* at room temperature was reduced to 500 pm/V compared to 700 pm/V in the undoped composition at 1 kV/mm. The electrostrain, however, was found to be less sensitive to mechanical prestresses, showing a plateau up to stresses of 80 MPa in both doped compositions. These effects were attributed to a reduction of the domain wall mobility due to a smaller grain size, charged defect dipoles and the proximity of the room-temperature measurements to the reduced ferroelectric-paraelectric phase transition temperature. The study reveals that the exceptionally large strains observed in BCZT rely on the instabilities around the polymorphic phase transition in the system. Aliovalent doping changes this sensitive system and reduces the electrostrain considerably. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: BZT-BCT; Doping; Piezoelectric properties; Lead-free; Ferroelasticity